SekaaMakepung Dalam Pemenangan Incumbent Pada Pilkada Serentak 2015 Di Kabupaten Jembrana - Gemet Permadi, I Made (Jurnal Nawala Politika, 2017)
Makepung is an original culture of Jembrana District which has aSekaa and spreads around Jembrana District then forms an organizational structure by utilizing the culture of Makepung. Makepung Culture became one of the political groups for Incumbent candidates to compete and direct all their social medias to gain power and resources in their area through Pilkada. Mass mobilization relation conducted by Incumbent candidates through Makepung’sSekaa-Sekaa in Jembrana District to win elections in en bloc Pilkada 2015. The purpose of this research is to find out how Makepung’sSekaa as a part of local culture used to mobilize mass in elections in en bloc Pilkada 2015 in Jembrana District. This research uses qualitative methodology and descriptive analysis. Primary data were collected through purposive sampling interview techniques, while secondary data were obtained from news articles, internet, and books related to this research. This study uses social capital theory by Putnam. The results of this study show; One, to see the interaction of Incumbent candidate toSekaaMakepung which caused the Incumbent candidate to provide assistance, the implementation to the attention toSekaaMakepung by using the power in the first period to create a social capital relationship from the thinking of Robert Putnam; Two, mass mobilization fromSekaaMakepung to Makepung fans, relatives, families and society spread in Jembrana District to choose Incumbent candidate who is carried bySekaaMakepung . Keywords:SekaaMakepung, Social Capital, Incumbent Candidate, Mobilisa massa